HIDROSTRATIGRAFI DAN GEOMETRI AKUIFER CEKUNGAN AIR TANAH PALU, PROVINSI SULAWESI TENGAH PASCA GEMPA BUMI - Derry Prasetya Putra Santosa; Mohamad Sapari Dwi Hadian; Zulfialdi Zakaria (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2021)
Palu Groundwater Basin can be assumed to have a post-earthquake deformation in 2018. To identify current state of Palu Groundwater Basin, modeling approach was conducted using GMS 10.4 (Groundwater Modeling System) with IDW (Inverse Distance Weighting), with the data used for the model was obtained from 41 boreholes. The results show that Palu Groundwater Basin aquifer geometry can be divided into 4 types. The unconfined aquifer consisting of Alluvium and Coastal Deposits (Qa) have an area 412,69 km², with 17,77 - 72.48 m thickness top layer have elevation 341 MSL (mean sea level) and bottom layer have elevation -2,29 MSL. Top aquitard consisting of Celebes Mollase of Sarasin and Sarasin (QTms) have an area 391,1 km² with 0.1 - 20,61 mm thickness top layer have elevation 268,52 MSL and the bottom of layer have elevation -20,06 MSL. Confined aquifer consisting of Celebes Mollase of Sarasin and Sarasin (QTms) have an area 351,98 km² with 20,58 - 86,51 m thickness top layer have elevation 268,42 MSL and bottom layer have elevation -40,67 msl. Bottom aquitard consisting of Granite and Granodiorite (Tmpi), Tinombo Formation (Tts), Metamorphic Complex (Km), Latimojong Formation (Kls) have an area 78,24 km² with 20,58 - 86,51 m thickness 3,01 - 4,1 m top layer have elevation 181,91 MSL and bottom layer have elevation -29,09 MSLKeywords: Groundwater, basin, modeling, geometry, aquifer